2021
DOI: 10.1177/00031348211031848
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Social Media Presence for Graduate Medical Education Programs

Abstract: Virtual residency interviews during COVID-19 pandemic created a need for residency programs to use social media to increase their visibility and connect with potential applicants. This was, however, new and a road never travelled for many programs. This report describes how our General Surgery Residency Program increased its presence through social media by using various exposure methods and approaches, including diversifying presence and developing candid personalized content. Results suggest that these metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In particular, they have found success with a video-based series presenting residents, faculty, and the program in a candid fashion. 16 Although our study has shown pictures to have more Twitter engagement (by likes and retweets) than videos, individual programs may find more success with one modality over another. Programs may not have the creative vision or expertise to create effective video-based content.…”
Section: Discussionmentioning
confidence: 59%
“…In particular, they have found success with a video-based series presenting residents, faculty, and the program in a candid fashion. 16 Although our study has shown pictures to have more Twitter engagement (by likes and retweets) than videos, individual programs may find more success with one modality over another. Programs may not have the creative vision or expertise to create effective video-based content.…”
Section: Discussionmentioning
confidence: 59%
“…Considering these findings and results from other studies, we propose four recommendations (Figure 1). 2,27,28,30,31,[34][35][36][37][38][39][40][41] Our study has several limitations. Given that survey participation was voluntary, there was potential for response bias towards applicants with particularly strong feelings about their Match experience.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the virtual interview process found that programs perceived they could present themselves and their program and assess applicant candidacy virtually [ 20 , 28 ]. During the pandemic, many institutions increased their social media presence to enrich the presentation of their program [ 29 , 30 ]. Despite early unfamiliarity with digital platforms, they are increasingly recognized as effective and efficient means of communication and assessment for recruitment [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, many institutions increased their social media presence to enrich the presentation of their program [ 29 , 30 ]. Despite early unfamiliarity with digital platforms, they are increasingly recognized as effective and efficient means of communication and assessment for recruitment [ 29 , 30 ]. There has been a move towards more holistic review rather than simple reliance on test scores for decisions regarding interviews [ 1 , 31 ].…”
Section: Discussionmentioning
confidence: 99%